2018
DOI: 10.1136/heartjnl-2018-313700
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 2014 European Society of Cardiology guideline on sudden cardiac death in hypertrophic cardiomyopathy: a systematic review and meta-analysis

Abstract: ObjectiveIn 2014, the European Society of Cardiology (ESC) recommended the use of a novel risk prediction model (HCM Risk-SCD) to guide use of implantable cardioverter defibrillators (ICD) for the primary prevention of sudden cardiac death (SCD) in patients with hypertrophic cardiomyopathy (HCM). We sought to determine the performance of HCM Risk-SCD by conducting a systematic review and meta-analysis of articles reporting on the prevalence of SCD within 5 years of evaluation in low, intermediate and high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Finally, a large multicentre, international study proved the positive impact of the HCM Risk-SCD prediction model in clinical decision-making 9. In addition, a systematic review and meta-analysis involving 7291 patients with HCM again recently reported the clinical value of the HCM Risk-SCD calculator 16…”
Section: Discussionmentioning
confidence: 98%
“…Finally, a large multicentre, international study proved the positive impact of the HCM Risk-SCD prediction model in clinical decision-making 9. In addition, a systematic review and meta-analysis involving 7291 patients with HCM again recently reported the clinical value of the HCM Risk-SCD calculator 16…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the metanalysis of six studies conducted with 7,291 patients demonstrates that in most cases, the five-year SCD risk is properly estimated with the ESC score. 33 The European score settles the stratification for SCD using a rigid statistical model in a complex disease with unpredictable course. Methodological limitations may depend on left atrial evaluation with diameter, LVOT obstruction with Valsalva maneuver, and on exclusion of myocardial ischemia, late gadolinium enhancement and LV apical aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The HCM risk SCD [66] is a risk prediction model for HCM that had been used to direct the use of implantable cardioverter defibrillators (ICDs) for the prevention of SCD. The risk prediction has been extensively tested for validation and shown to be the best available risk predictor [67,68]. As of now, OSA is not part of the ESC risk calculator, but it could become a part of the prediction model in the future when studies could potentially show evidence of OSA increasing SCD risk.…”
Section: Prevention Of Scdmentioning
confidence: 99%